The participation of hard-to-reach older people in the research and development process of health technologies from the perspective of multipliers—A qualitative analysis - Pauls, Alexander; Koppelin, Frauke; Zeeb, Hajo (Frontiers in Public Health, 2024)
The participation of older people in research and development processes has long been called for but has not been sufficiently put into practice. In addition, participation is often late and not particularly intensive, so that certain older groups of people are underrepresented in the development of health technologies (HT). Heterogeneity, e.g. between urban and rural populations, in access to and motivation for participation is also rarely taken into account. The aim of this study was to investigate form and phases of participation for hard-to-reach older people in the research and development process of HT.The qualitative study among multipliers was conducted using focus groups and telephone interviews and took place in a city and an adjacent rural area in northwestern Lower Saxony, Germany. A content analysis of the data was undertaken using deductive-inductive category formation.Results: 17 participants (13 female) took part in the study (median age 61, 33-73). Participants from both areas identified particular forms and phases of participation in the research and development process. Longer forms of participation for hard-to-reach groups and the development process of technologies for older people from the rural area were viewed as challenges. Passive and active access strategies are needed to achieve sufficient heterogeneity in the research and development process. Trusted multipliers can play an important role in gaining access to hard-to-reach older people, but also during the research process. Apart from facilitating factors (e.g., age-specific study materials), inhibiting factors such as contact anxieties are also indicated. Only urban participants mention financial/material incentives and community as possible motivations.The results provide important insights from the perspective of multipliers. They show specificities in access and participation for rural areas and for hard-to-reach older people. Many older people may have uncertainties about research projects and HT. Multipliers can assume a key role to help reduce these uncertainties in the future.